Feeding Behavior of Brown Planthopper (Nilaparvata lugens) on Pigmented Rice Monitored by Electrical Penetration Graph (EPG) - Witjaksono, Witjaksono; Aldawood, Abdulrahman Saad; Kristamtini, Kristamtini; Sumarno, Sumarno; Andriyanto, Rofiq; Soffan, Alan (Universitas Gadjah Mada, 2024)
Rice is one of the essential daily commodity for most of Asian. However, the brown plant hopper (BPH; Nilaparvata lugens) infestation had been threatening the increasing demand of rice production. Evaluating resistance level of rice cultivars against BPH will help in managing BPH infestation. The feeding behavior monitoring of brown plant hopper (BPH; Nilaparvata lugens) by using an electrical penetration graph (EPG) was conducted to evaluate the resistance level of several rice cultivars against BPH, including pigmented rice (black rice cv. Sembada hitam; red rice cv. Sembada merah); and the commonly consumed white rice (cv. Ciherang). The EPG instrument allowed the monitoring of BPH feeding behaviors by quantifying three unique waveforms, namely, N3, N4, and N5, which represent BPH feeding activities in areas near phloem tissues, in phloem tissues, and in xylem tissues, respectively. EPG monitoring of BPH feeding activities in black rice revealed the absence of the N3 and N4 waveforms. Red rice showed the N3 waveform but not the N4 waveform. White rice showed all three waveforms occurring with high numbers and long total durations. The absence of the N4 waveform in the two pigmented rice cultivars indicated the failure of BPH to access phloem tissues. Overall, the results revealed that the resistance of rice against BPH based on feeding activity could be ordered as follows: black rice > red rice > white rice. This report provides essential information on the resistance mechanism of pigmented rice cultivars against BPH.